Investigation And Performance Optimization Of Propulsion System For An Indoor Plane - Teoh, Len Choon (Universiti Sains Malaysia, 2017)
This research focus on the propulsion system for a Mini Stick scale indoor plane which consists of a rubber band and a propeller. The effect of the rubber band on the performance of the indoor plane is analyzed by using a torque meter. Different thickness and thickness of rubber band are tested to search for the most suitable thickness and length of rubber band that is able to sustain the rotation of propeller for 5 minutes. The factors that affect the thrust generated by the propeller are studied through numerical solution and experimental analysis. The numerical solution is done by using MATLAB programming software and some assumptions are made to simplify the analysis as well as the algorithm. The experimental analysis is done by using the load balance and the propeller is tested at different pitch angle with different thickness of rubber band. From the research, the torque of the rubber band increases with the thickness of the rubber band and the thrust generated by the propeller increases with the pitch angle of the propeller. However, the torque and the thrust must be in an optimum value. This is because a high torque will use up the energy stored in a rubber band at a faster rate and a high thrust will causes the indoor planes to accelerate. Both of these will lead to poor endurance performance of an indoor plane. Hence, for the propeller for an indoor plane to sustain for 5 minutes, the most suitable thickness of rubber band is 1.5875 mm and winded up to 3300 turns. The pitch angle of the propeller blade must be in 48°. This research can be further improved by designing the propeller blade into different geometry. For example, an elliptical-shaped propeller will reduce the tip vortex which might contribute to a better performance of propeller for an indoor plane.